Electrodeposition of 1-D Tellurium Nanostructure on Gold Surface from Choline Chloride-Urea and Choline Chloride-Ethylene Glycol Mixtures - Casagrande-Denardin, J; Melo-Freire, R (Elsevier B.V., 2019)
The electrodeposition of Te on Au substrate was investigated in either choline chloride-urea and in choline chloride-ethylene glycol deep eutectic solvents, at a molar ration of 1:2, containing 0.05 mol L−1 TeCl4. The electrodeposition of Te on Au electrode followed a three-dimensional progressive nucleation mechanism in both eutectic solvents. The diffusion coefficients of Te4+ species as a function of temperature were well fitted by a like-Arrhenius equation in both plating solutions. The apparent activation energies were 22.20 and 22.55 kJ mol−1 for Scharifker-Hills and Cottrell s models, respectively, in 1ChCl:2EG. On the other hand, in 1ChCl:2 U these values were 59.20 and 57.80 kJ mol−1. In addition, SEM micrographs of Te electrodeposits from both revealed a large-scale Te rods-like morphology with hexagonal cross-section in nanoscale regime uniformly distributed on electrode surface. TEM investigation suggested that Te single-crystalline grew perpendicular direction of (100) planes which implied in the preferential growth direction of [001]. © 2019 Elsevier B.V.